1979
DOI: 10.1002/ange.19790910324
|View full text |Cite
|
Sign up to set email alerts
|

Dianion und Tetraanion von Octalen

Abstract: Die Atomabstande in ( 2 ) , B = PPh3, sprechen fur eine mesoionische Formulierung des Komplexes : Die P-As-Bindungslange stimmt ungefahr rnit der Summe der K~valenzradien[~"] uberein, was auf eine hohe positive Teilladung am Phosphoniumpol schliel3en 1aBt. Auch die kurzen P-Cph-Abstande und die groBen CPC-Winkel stutzen diese D e~t u n g [~~] .Die positive Teilladung des Phosphors wird durch das 31P-NMR-Signal bestatigt, das rnit 6= 11.8 (rel. H3P04 ext.) gegenuber dem Signal von PPh3 bei 6 = -7 eine Tieffeld… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In addition, recording the intermediate NMR and ESR spectra can tell a lot about the rates of electron transfer as well as about the relative energies of the species involved. 156 When treating cyclooctatetraene (3) in tetrahydrofuran (THF) with potassium, one observes the following 7H NMR spectroscopic behavior of the system:7 (1) the sharp resonance of 3 decreases in intensity without significant line broadening; (2) after the signal has decreased to less than about 10% of its original intensity a very broad absorption is superimposed on the initial peak; (3) the latter disappears while the broad absorption, which is assigned to the dianion 32-, narrows; (4) the resulting sharp singlet has the same intensity as that of the starting material.…”
Section: B Kinetics Of Electron Transfer and Disproportionation Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, recording the intermediate NMR and ESR spectra can tell a lot about the rates of electron transfer as well as about the relative energies of the species involved. 156 When treating cyclooctatetraene (3) in tetrahydrofuran (THF) with potassium, one observes the following 7H NMR spectroscopic behavior of the system:7 (1) the sharp resonance of 3 decreases in intensity without significant line broadening; (2) after the signal has decreased to less than about 10% of its original intensity a very broad absorption is superimposed on the initial peak; (3) the latter disappears while the broad absorption, which is assigned to the dianion 32-, narrows; (4) the resulting sharp singlet has the same intensity as that of the starting material.…”
Section: B Kinetics Of Electron Transfer and Disproportionation Effectsmentioning
confidence: 99%
“…Electrochemical measurements suggested that 115 should form a radical anion, a dianion, a radical trianion, and a tetraanion, and, indeed, one can prepare and spectroscopically characterize all of these species. 156 The identification of the single products follows from the same arguments that have been discussed in section II.…”
Section: H52" Bmentioning
confidence: 99%